Efeito do plasma rico em glicose na apoptose de neutrófilos de cães - Nogueira, Maria Carolina Ramos [UNESP]; Pereira, Priscila Preve [UNESP]; Almeida, Breno Fernando Martins de [UNESP]; Bosco, Anelise Maria [UNESP]; Barbosa, Tatiana Souza [UNESP]; Ciarlini, Paulo César [UNESP] (Universidade Federal do Paraná, 2013)
Hyperglycemia is considered the main cause of increased mortality in diabetic humans, to promote the acceleration of neutrophil apoptosis, essential for the functioning of the immune system. Thus, there is an immunosuppressive effect that contributes to the increased susceptibility of patients to serious bacterial infections. In canine species there is no similar studies on the immunosuppressive effect of hyperglycemia, so that it tested the hypothesis that excess glucose accelerates neutrophil apoptosis in dogs. To this end, replaced the plasma of blood samples from 10 healthy dogs plasma autologous, homologous counterpart normoglycemia and hyperglycemia. All samples were incubated for two and four hours.The glucose measurements were performed using kinetic glucose oxidase and neutrophil apoptotic index calculated by the morphometric method. In all tests the apoptotic index increased after two and four hours. After four hours, the apoptotic index of the samples incubated with homologous plasma hyperglycemia was significantly higher (p <0.05) to the samples incubated with homologous and autologous normoglycemia. It was concluded that plasma hyperglycemia in vitro increases the rate of neutrophil apoptosis in dogs, strengthening the hypothesis that dogs with hyperglycemic disease may also suffer immunosuppression neutrophil dysfunction.

A hiperglicemia é considerada a principal causa do aumento da mortalidade em pacientes diabéticos humanos, por promover a aceleração da apoptose dos neutrófilos, essenciais para o funcionamento do sistema imune. Desta forma, dá-se um efeito imunossupressor que contribui para o aumento da susceptibilidade dos pacientes a infecções bacterianas graves. Na espécie canina não há estudos semelhantes quanto ao efeito imunossupressor da hiperglicemia, de modo que se testou a hipótese de que o excesso de glicose acelera a apoptose dos neutrófilos em cães. Para tal, substituiu-se o plasma de amostras de sangue de 10 cães sadios por plasma autólogo, homólogo normoglicêmico e homólogo hiperglicêmico. Todas as amostras foram incubadas por duas e quatro horas. As mensurações de glicose foram realizadas pelo método cinético glicose oxidase e o índice apoptótico dos neutrófilos calculado pelo método morfométrico. Em todos os ensaios o índice apoptótico aumentou após duas e quatro horas. Após quatro horas, o índice apoptótico das amostras incubadas com plasma homólogo hiperglicêmico foi significativamente superior (p<0,05) aos das amostras incubadas com homólogo normoglicêmico e autólogo. Concluiu-se que in vitro o plasma hiperglicêmico aumenta a taxa de apoptose dos neutrófilos em cães, fortalecendo a hipótese de que cães portadores de doenças hiperglicemiantes possam igualmente sofrer imunossupressão por disfunções neutrofílica.
Effect of rich glucose plasma in apoptosis of neutrophils in dogs
Keywords: Hyperglycemia; Immunosuppression; Polymorphonuclear; Hiperglicemia; Imunossupressão; Polimorfonuclear